The importance of energy-differential cross sections highlighted in a benchmark for positronium formation in the Galaxy. Issue 15 (January 2020) - Cocks, D G; Chaudhary, H; Machacek, J R
Synopsis: We detail a benchmark model aimed at improving the implementation of Monte Carlo codes for simulations of positrons propagating through interstellar media. The benchmark highlights the key features of cross sections sets which lead to major differences in astronomical observables. One of these is the energy-differentiation of the ionisation cross section. This leads us to call for improved cross section sets for all constituents of interstellar media.